Media History Fun Thinkers untuk Meningkatkan Keterampilan 4 C dan Hasil Belajar IPS - Mistina Hidayati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The problems of social teaching learning in SMP N 1 Banyumas are the low 4C skills (Communication, Collaboration, Critical Thinking and Problem Solving, and Creativity and Innovation). Classroom Action Research aims to provide an overview of (1) the learning process using media History Fun Thinkers to improve 4 C skills and learning outcomes (2) increase skills 4 C and social studies learning outcomes with media History Fun Thinkers, and (3) results / the impact of the application of the learning process using History Fun Thinkers. This research was designed in two cycles. Each cycle consists of four stages starting from planning, implementation, observation and reflection. The results showed that, (1) 4 C skills increased from 62.70% before the cycle, 83.20% in the first cycle and 92.19% in the second cycle. (2) learning outcomes increased from the total completeness of 59.38% before the cycle becomes 78.13% in the first cycle and 93.75% in the second cycle. (3) the behavior of students experiences positive changes with better character formation.